Exploring the Archetypes of Initiation and Wise Old Man in C. S. Lewis’s The Chronicles of Narnia - Jafari, Bahereh Mehdizadeh (2010)
This study scrutinizes C. S. Lewis’s The Chronicles of Narnia through the archetypal framework, focusing on the two major archetypal motifs of Initiation and the Wise Old Man. The archetype of Initiation is traceable in almost all the adventures of the novices of this collection of stories and this study shows how such initiation takes the initiates from immaturity to maturity, when they achieve self-discovery and find their true selves. To explore the archetype of Initiation in the selected texts, this study uses Henderson’s theory of initiation which offers three stages for achieving initiation: Submission, Containment-Release and Immanence. The literature review looks at other relevant researches on the Chronicles, and explores some relevant explications of the major works of Jung, Campbell, van Gennep and Henderson on initiation. From the archetype of Initiation, this study moves on to explore the archetype of Wise Old Man in relation to the presentation of the adventurers in the Chronicles - how the archetype of the Wise Old Man is represented in various forms, based on Jung’s viewpoint – coming to the rescue of the adventurers when they are confused and lost or when they are faced with indomitable challenges. Through textual evidence, this study shows how the Wise Old Man – whether in the form of Aslan, a talking lion, a teacher, or a venerable old man – is there for the heroes or heroines, to dispense knowledge, wisdom, or advice to enable them to complete their missions successfully. This study shows how Lewis, in the Chronicles, uses the genre of the archetypes of Initiation and the Wise Old Man to tell stories that express moral and spiritual values that appeal universally, not only to children, but also adults. Employing the two archetypes in the study allows for a deeper insight and a better understanding of The Chronicles of Narnia.